A novel image encryption using an integration technique of blocks rotation based on the Magic cube and the AES Algorithm - Abugharsa, Ahmed Bashir; Hasan Basari, Abd Samad; Almangush, Hamida (IJCSI, 2012)
In recent years, several encryption algorithms have been proposed to protect digital images from cryptographic attacks. These encryption algorithms typically use a relatively small key space and therefore, provide safe, especially if they are of a dimension. In this paper proposes an encryption algorithm for a new image protection scheme based on the rotation of the faces of a Magic Cube. The original image is divided into six subimages and these sub-images are divided amongst a number of blocks and attached to the faces of a Magic Cube. The faces are then scrambled using rotation of the Magic Cube. Then the rotated image is fed to the AES algorithm which is applied to the pixels of the image to encrypt the scrambled image. Finally, experimental results and security analysis show that the proposed image encryption scheme not only encrypts the picture to achieve perfect hiding, but the algorithm can also withstand exhaustive, statistical and differential attacks.